An evaluation of the implementation of quality improvement (QI) in primary care dentistry: a multi-method approach. Issue 2 (13th April 2021) - Cassie, Heather; Mistry, Vinay; Beaton, Laura; Black, Irene; Clarkson, Janet E; Young, Linda
Abstract : Objectives: Ensuring that healthcare is patient-centred, safe and harm free is the cornerstone of the NHS. The Scottish Patient Safety Programme (SPSP) is a national initiative to support the provision of safe, high-quality care. SPSP promotes a coordinated approach to quality improvement (QI) in primary care by providing evidence-based methods, such as the Institute for Healthcare Improvement's Breakthrough Series Collaborative methodology. These methods are relatively untested within dentistry. The aim of this study was to evaluate the impact to inform the development and implementation of improvement collaboratives as a means for QI in primary care dentistry. Design: A multimethod study underpinned by the Theoretical Domains Framework and the Kirkpatrick model. Quantitative data were collected using baseline and follow-up questionnaires, designed to explore beliefs and behaviours towards improving quality in practice. Qualitative data were gathered using interviews with dental team members and practice-based case studies. Results: One hundred and eleven dental team members completed the baseline questionnaire. Follow-up questionnaires were returned by 79 team members. Twelve practices, including two case studies, participated in evaluation interviews. Findings identified positive beliefs and increased knowledge and skills towards QI, as well as increased confidence about using QI methodologies in practice. Barriers included time, poor patient and team engagement, communication and leadership. Facilitators included team working, clear roles, strong leadership, training, peer support and visible benefits. Participants' knowledge and skills were identified as an area for improvement. Conclusions: Findings demonstrate increased knowledge, skills and confidence in relation to QI methodology and highlight areas for improvement. This is an example of partnership working between the Scottish Government and NHSScotland towards a shared ambition to provide safe care to every patient. More work is required to evaluate the sustainability and transferability of improvement collaboratives as a means for QI in dentistry and wider primary care.